The Influence of Financial Literacy, Lifestyle and Environment on the Personal Financial Management of Accounting Students at Politeknik Negeri Tanah Laut - Febrianti, Norliana; Amelia, Noor; Suasri, Eni; Hadiani, Yasir (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
Personal financial management is one of the financial intelligences possessed by humans, including students. Personal financial management can be influenced by various factors. Factors that are thought to influence personal financial management include financial literacy, lifestyle and environment. The population in this study were regular active students of the D3 Accounting Study Program in semesters 4 and 6. Meanwhile, the sample in this study was 143 people. The data collection technique in this research uses primary data by distributing questionnaires. The data analysis techniques used are data quality testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that partially, financial literacy and lifestyle results have no effect on the level of awareness of personal financial management, while environmental results have an effect on the level of awareness of personal financial management. Meanwhile, based on the results of simultaneous tests, financial literacy, lifestyle and environmental variables influence personal financial management variables. It is known that the R- Square value is36.3%. Meanwhile, the remaining 63.7% was influenced by other causes outside this research model.